GLOBALISASI : INTERVENSI KEKUATAN POLITIK DAN EKONOMI DALAM PEMBENTUKAN HUKUM DAN PENGUSAHAAN MIGAS DI INDONESIA - ., Sugiaryo (MAGISTRA, 2010)
The relation of international economical and politic in globalization era is indeed very closely. Both ofthem have causal inter-influencing and dynamic in their natures. Big and strong countries are much moreprovide  their  influences,  even frequently  insisting  on  their  intention  using  varied  premises.  The  frequentlyproposed premised are in relation with human rights. Conversely, small countries, developing countries andpolitically and economically weak countries are much more depending on global level. The oil and gas lawestablishment in Indonesia, United States through USAID, in cooperation with Indonesian governmental officerswith the involvement of NGO, universities and media provide funds to arrange draft of Oil and Gas Acts yearof 2000. The draft of Oil and Gas Acts thereafter had stipulated to be the Acts NO. 22/2001. In this Acts, thereare orders from United States especially in Article 28 verse 2 in which confirming that prices of fuel and oil andalso earth gas is delegated to health and fair business competition mechanism. For such importance, for it canbe successful, then there also emerging a policy that each debt from IMF, World Bank and ADB had conditionedthat the debtor must implement privatization, deregulation and fuel and oil subsidy cancellation to follow themarket price.Although the Acts No. 22/2001 had been stipulated, but in the implementation, specifically for article 28verse 2 and verse 3, they have been experience obstruction due to Pertamina Unions had proposed accusationto the Court of Constitution on the violation of such acts with the Article 33 of 1945 Constitution. And in thetrial results by the Court of Constitution, the article 28 verse 2 and verse 3 had cancelled and having no legalauthorization.The cancellation of the article by the Court of Constitution, in fact, is not giving obstruction for theUnited States wish to hold intervention because they keep try in substituting a new term, that is the term marketprice which by the Court of Constitution had been banned is replaced with the term economical price. It isshown from the governmental policy in 2005, 2007 and 2009 which stated the price increment on oil and fuel,especially subsidized premium. And if in last 1 December 2008 the price decreased, and furthermore decreasedin 15 December 2008, they were due to the decrement of world oil price.Keywords: Globalization, intervention, political and economical power, law establishment and oil and gasbusiness